2012
DOI: 10.1097/spv.0b013e318249bd54
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Operative Technique on Mesh Exposure in Laparoscopic Sacrocolpopexy

Abstract: We found that preserving the integrity of the vaginal cuff led to a lower incidence of mesh exposure in patients undergoing laparoscopic sacrocolpopexy. When hysterectomy is indicated, a supracervical technique should be strongly considered as the mesh exposure rate was significantly lower. If removal of the cervix is indicated, the risk for mesh exposure remains low and should not preclude total hysterectomy, though transvaginal mesh attachment may be preferable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 9 publications
3
41
0
Order By: Relevance
“…The frequency of mesh exposure after LSC observed in the present study (0.88%) is similar to previous data. 21 One study has discussed The present data revealed that both procedures improved quality of life, in line with another report. 13 However, LSC/LSH was effective only in alleviation of POP symptoms, whereas VSSLF yielded significant improvements in organ descent, and colorectal-anal and urinary symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The frequency of mesh exposure after LSC observed in the present study (0.88%) is similar to previous data. 21 One study has discussed The present data revealed that both procedures improved quality of life, in line with another report. 13 However, LSC/LSH was effective only in alleviation of POP symptoms, whereas VSSLF yielded significant improvements in organ descent, and colorectal-anal and urinary symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, none of the 11 patients who underwent LSH experienced recurrence of POP after surgery, supporting the study of Mourik et al., who reported that LSH is an effective treatment for POP with 95.3% patient satisfaction. The frequency of mesh exposure after LSC observed in the present study (0.88%) is similar to previous data . One study has discussed concerns that surgical interventions for POP performed concomitantly with hysterectomy might increase the risk of infection and graft exposure, due to surgical field contamination from vaginal flora while opening the vaginal cuff …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The most significant risk factor for extrusion in our study was concomitant hysterectomy, which was also seen in 2 recent studies of women undergoing minimally invasive sacral colpopexy. 13,15 Although our data did not specifically address mode of hysterectomy, some surgeons perform a supracervical approach if hysterectomy is indicated at the time of ASC because there are some data to support this approach to avoid mesh extrusion at the apex. 13 The risk of mesh extrusion with total hysterectomy must be weighed against the risks of cervical preservation, including potential future cervical pathology and/or bleeding as well as the patient's desires.…”
Section: Discussionmentioning
confidence: 95%
“…In a recent study by William et al with median follow up of 26 weeks concluded that preserving the vault integrity led to lower incidence of mesh exposure in patient undergoing LSCP and when hysterectomy was indicated supracervical technique should be considered as the incidence of mesh exposure was lower. If cervix needs to be removed due to various reasons then (vaginal assisted laparoscopic sacrocolpopexy) transvaginal attachment of mesh has lower rate of mesh exposure compared to (vaginal hysterectomy laparoscopic sacrocolpopexy) [23].…”
Section: Discussionmentioning
confidence: 99%